Issues surrounding data subject consent as a lawful basis for the processing of personal data in the European Union - Oginska, Sanda (Riga Graduate School of Law, 2021)
Individuals being in control of the given consent for the processing of their personal data sounds great in theory, in reality however, there are some issues surrounding data subject consent as a lawful basis for the processing of personal data in the European Union under the GDPR. The aim of this research is to find out and analyze these issues by challenging the different legal opinions thereof and offering an informed critique of the current law. According to the results of the study, there are issues around these sections: 1) substantive legal conditions for consent 2) procedural conditions for consent 3) technology based aspects and behavioural aspects of individuals. The conclusion of this research is that it is necessary for individuals, society and businesses to improve consent literacy
Keywords: Data protection